Contract administration - Davies, Ian (Architect) (RIBA plan of work., 2014)
The RIBA plan of Work 2013 Guide: Design Management is part of a brand new series providing must-read practical guidance to running efficient and successful projects using the new RIBA Plan of Work 2013. Each guide takes a core project task - in this case the role of the Contract Administrator - and explains the essential activities and considerations required at each stage of the new Plan of Work. Easy to use and navigate and in a small and handy format these guides will provide the ultimate quick reference support at your desk or on site. The author provides concise and pragmatic advice rooted in real world experience - a 'how to' that will resonate with practitioners. In-text features such as 'hints and tips', 'checklists', 'forms and templates' and 'signposts' to trusted resources will provide user-friendly support. Boxed examples will highlight best practice and illuminate common problems and solutions borne of hard won experience. These guides are designed to be used on all projects - large and small - and across all types of procurement. They are task rather than role-oriented acknowledging that a variety of people take on these responsibilities including the architect, the client, the contractor or a consultant. They will also be useful for architectural students at Part 3 who are getting to grips with the realities of practice and the new Plan of Work. The author and series editor, Dale Sinclair, is a highly successful and experienced practitioner, lecturer and author. He is RIBA Vice President, Practice and Profession, and he led the development of the RIBA Plan of Work 2013.